Application of dispersive liquid-liquid microextraction based on solidification of floating organic droplet to the analysis of antidepressant drugs in water samples - Mohd Marsin Sanagi,; Siti Umairah Mokhtar,; Wan Aini Wan Ibrahim,; Hassan Y. Aboul-Enein, (Universiti Kebangsaan Malaysia, 2013)
A simple and rapid sample preparation method based on dispersive liquid-liquid microextraction-solidification of floating organic drop (DLLME-SFO) combined with gas chromatography-mass spectrometry (GC-MS) method was developed for the analysis of antidepressant drugs in water samples. This method uses organic solvent with low density and less toxicity. In the method, the disperser solvent (0.5 mL acetonitrile) containing 30 μL of n-hexadecane was rapidly injected using a syringe into 5.0 mL of water sample in a glass tube. After centrifugation for 7 min at 3,500 rpm, the mixture was cooled in ice bath for 5 min. The solidified n-hexadecane was transferred into a conical vial, where it melted rapidly at room temperature and 2 μL of it was injected into a gas chromatograph for analysis. Under optimized conditions, the method showed good linearity in the range of 0.04 - 0.12 μg mL-1 for amitriptyline and chlorpromazine with correlation of determination (r2) in the range of 0.992 - 0.995. The limits of detections (LODs) were in the range 0.0085 - 0.0285 μg mL-1. The extraction recoveries of amitriptyline and chlorpromazine from water samples at spiking level of 0.08 μg mL-1 were 71.34 - 73.52% and 73.83 - 91.09%, respectively, with relative standard deviations (RSDs) in the range of 4.97 - 6.85% for amitriptyline and 4.84 - 7.49% for chlorpromazine. The method was successfully applied to the determination of the analytes in drinking water, lake water and tap water samples.